Skin necrosis following sclerotherapy. Part 1: Differential diagnosis based on classification of pathogenic mechanisms. (July 2022) - Kang, Mina; Yang, Anes; Hannaford, Patricia; Connor, David; Parsi, Kurosh
Background: Tissue necrosis is a significant but uncommon complication of sclerotherapy. The pathogenic mechanisms of this often-debilitating complication have been poorly described in the literature. Purpose: To elucidate the pathological mechanisms, we propose a morphological approach to classify sclerotherapy-induced skin necrosis into two categories of round and stellate (star-like) necrosis. Research Design: Comprehensive literature review was conducted. Results: Round necrosis is typically caused by extravasation of sclerosants. It typically presents as an ulcer with smooth and non-geographic borders. Historically, extravasation has been cited as the main cause of sclerotherapy-related necrosis. While this may be the case with osmotic or irritant sclerosants, it is far less likely with the use of detergent agents particularly in the foam format.The more commonly encountered pattern of stellate necrosis is an ischaemic ulcer secondary to arterial/arteriolar occlusion. In contrast to round necrosis, stellate necrosis follows an intra-vascular injection of sclerosants such as an inadvertent intra-arterial injection. But more frequently, stellate necrosis may follow a perfectly executed intra-venous or intra-telangiectatic delivery of sclerosants. Several pathogenic pathways can be considered. The physiologic response of veno-arteriolar reflex vasospasm (VAR-VAS) is possibly the most frequent pathway. It follows a high-pressure injection of the sclerosant in a target vein resulting in a rapid rise of intravenous pressures which in-turn would trigger a sympathetic neuronal reflex vasospasm of the pre-capillary sphincters and a corresponding opening of the normally closed arterio-venous anastomoses (AVAs). This communication would allow entry of the sclerosing agent into the arteriolar side of the circulation resulting in arteriolar occlusion and infarction of the corresponding skin. Similarly, an intravenous administration of sclerosants in the vicinity of defective boundary valves or persistently open AVAs can result in the entry of detergent agents into the arteriolar side of the microvasculature causing an ischemic stellate ulcer. Conclusions: In this first instalment of these two-part series, we review the pathogenic mechanisms of post-sclerotherapy necrosis. In the second instalment, we describe risk minimisation and management strategies.